Blackout Periods in GRA Arrangements and the Extended Rights to Purchase Policy : A Review. (Policy Papers; Policy Paper ;, 2013)
This paper reviews the IMF's extended rights to purchase (ERP) policy. Established in 2009, the ERP policy extends the continuity of purchase rights during temporary interruptions of access to previously accumulated, but undrawn, balances which occur during periods where data on relevant periodic performance criteria (PCs) is not yet available. This policy specifically provides for access to accumulated but undrawn purchase rights under SBAs and arrangements under the EFF (?extended arrangements?). While enhancing the continuity of a member's purchase rights, the ERP policy also provides several safeguards aimed at reducing the risk that a member might draw on Fund resources when its Fund-supported program goes off track.